Investigation of changes in nutritional status and anthropometric measurements depending on the menstrual cycle in women: A cross-sectional study - Hızlı, Hilal; Kıyak, Şule; Ertosun, Ahsen Fulya; Eryılmaz, İlkay; Gasanova, Parikhonum (My University, 2020)
Objective: The primary aim of this study is to investigate the nutritional status and body composition changes of 80 Turkish women within the age of 18-25 years during their menstrual cycles. Materials and Methods: Demographical and food intake behavior data were collected by a public survey. Body measurements of women were obtained 2 times; during and after the next four days of menstruation by BIA. Food intake records were taken to analzye energy and nutrient intakes. SPSS 18.0 program was used for statistical analyses. Results: The average age of participants was found 21.6 ± 1.68 years. Comparing women in during and after menstrual cycle, their body weight, waist circumference and chest circumference increments were found 0.32 kg, 0.90 cm and 0.57 cm respectively. These changes were statistically significant (p<0.05). Energy, carbohydrate and protein intakes elevated between two cycles, whereas fat intake was lower in menstrual phase, however no statistical significance was observed (p>0.05). Conclusions: Although various previous studies focused on the menstruation period, the novelty of our study lies within multiple parameters that we correleated, especially nutrient intake. There was no difference in energy and nutrient intake of women depending on the menstruation periods.

Amaç: Bu çalışmanın temel amacı, 18-25 yaşları arasındaki 80 Türk kadının, menstrüel siklusları boyunca beslenme durumlarını ve vücut kompozisyonlarındaki değişimleri araştırmaktır. Materyal ve Metot: Demografik bilgiler ve besin alımı verileri önceden yapılandırılmış bir anketle toplanmıştır. Kadınların vücut ölçümleri BIA yöntemiyle, menstruasyon sırasında ve sonrasındaki 4 günde olmak üzere 2 kez alınmıştır. Besin tüketim kayıtları analiz edilerek enerji ve besin öğesi alımları değerlendirilmiştir. İstatistiksel analizlerde SPSS 18.0 programı kullanılmıştır. Bulgular: Katılımcıların yaş ortalaması 21.6 ± 1.68 yıldır. Menstruasyon döngüsü sırasındaki ve sonrasındaki ölçümleri karşılaştırıldığında, vücut ağırlıkları, bel çevresi ve göğüs çevresi artışları sırasıyla 0.32 kg, 0.90 cm ve 0.57 cm bulunmuştur. Bu değişiklikler istatistiksel olarak anlamlıdır (p <0.05). Enerji, karbonhidrat ve protein alımları iki döngü arasında yükselirken, menstrüel fazda yağ alımı daha düşüktür, ancak istatistiksel olarak anlamlılık görülmemiştir (p> 0.05). Sonuç: Her ne kadar çeşitli çalışmalar menstruasyon dönemine odaklanmış olsa da, çalışmamızın yeniliği, özellikle bu dönemde besin öğesi alımını da değerlendirmesidir. Menstruasyon döngüsüne bağlı olarak kadınların enerji ve besin öğesi alımlarında farklılık olmadığı görülmüştür.
Keywords: Body Composition; Nutrients; Menstruation; Nutrition; Beslenme; Besin Öğesi; Menstruasyon; Vücut Kompozisyonu